2020
DOI: 10.1108/sc-03-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of safety among visitors to China: feeling safe in an unfamiliar environment

Abstract: Purpose The purpose of this paper is to address four questions: Firstly, how do tourists perceive safety from crime, specifically from robbery or violence, alongside other safety concerns? Secondly, are those who are concerned about crime also concerned about other threats to their well-being? Thirdly, how are their perceptions of safety affected by their perceptions of the local community? Finally, how are their perceptions affected by their personal and touristic characteristics? Design/methodology/approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Similarly, it is perceived that there is a higher probability of the elderly being victimised than young people (Scarborough et al, 2010). Apart from these demographic characteristics, personal experience may also significantly influence one's perceived safety (Zou and Mawby, 2020). Odufuwa et al (2019) found that frequent users felt safer than those less familiar with a place.…”
Section: Individual and Environmental Factors Of Fear Of Crimementioning
confidence: 99%
“…Similarly, it is perceived that there is a higher probability of the elderly being victimised than young people (Scarborough et al, 2010). Apart from these demographic characteristics, personal experience may also significantly influence one's perceived safety (Zou and Mawby, 2020). Odufuwa et al (2019) found that frequent users felt safer than those less familiar with a place.…”
Section: Individual and Environmental Factors Of Fear Of Crimementioning
confidence: 99%
“…A recent study on "sense of safety" revealed a strong tendency of low safety perceptions affecting German tourists' behaviour in Turkey and in Egypt destinations (Isaac and Velden, 2018) and among Dutch tourists in Sri Lankan markets (Isaac and Van der Bedem, 2020). A similar work amongst Chinese nationals in unfamiliar environments revealed concerns about safety and issues on reliability of information in the tourist destinations (Zou and Meng, 2019;Zou and Mawby, 2020). Most of such studies, however, are within different destination contexts, leaving a gap for further studies from the perspectives of migrant visitors in a developing country, such as Ghana.…”
Section: Sense Of Safety Trustworthiness Of Tourism Informationmentioning
confidence: 96%
“…Their feeling of security has been severely tested as the frequency and intensity of disasters have increased (Fang, 2020). For obvious reasons, tourists continue to prioritise safety and security concerns in their trip planning (Agarwal et al, 2021;Mawby and Vakhitova, 2022;Zou and Mawby, 2020). On the supply side, destinations deemed dangerous have been known to lose visitor appeal and, as a result, patronage (Cohen, 2019;Lisowska, 2017).…”
Section: Introductionmentioning
confidence: 99%